A review of the Kondo insulator materials class of strongly correlated electron systems: Selected systems and anomalous behavior - Strydom, A. M. (Frontiers in Physics, 2023)
Studies of strongly correlated electron systems have been at the forefront of research in condensed matter physics ever since the discovery of the co-existence of strong Pauli-paramagnetism and superconductivity in the heavy-fermion compound CeCu2Si2 in 1979. The construct of correlated electron physics typifies the behavior of thermal and electronic properties of a material when the Coulomb interaction between conduction electrons exceeds the electron kinetic energy at a given thermal energy, and redefines in remarkable ways our understanding of the behavior of a metal near its ground state. In a small number of cases the Kondo state forms of a very narrow energy band gap at the Fermi energy with consequences in the electrical resistivity, heat capacity, and magnetic susceptibility. Band gapping gives cause to the term Kondo insulator. Whereas the Kondo lattice ground state is exemplified by a very high density of electronic states at the Fermi energy, Kondo insulators on the other hand have a low density of electronic states. Kondo insulators have strong spin polarization energy scales and high values of their Kondo temperature which is an organizing principle in their physical characteristics. In this manuscript we review the fundamentals of the Kondo insulating state, and we discuss the theoretical principles of what is understood about Kondo insulators. Experimental results of a selected number of examples that have gained prominence in this class of materials are compared to each other in order to seek out similarities that may help to deepen our understanding of the Kondo insulating state.